Clock transcription factor CCA1 is regulated through sumoylation - Hansen, Louise Lipczak (The University of Edinburgh, 2017)
The circadian clock is an endogenous timekeeper that synchronises biological processes with daily external rhythms such as light and temperature cycles. It provides organisms with a competitive advantage by allowing anticipation of daily events. The circadian clock encompasses a network of transcription-translational feedback loops (TTFLs) that orchestrates rhythmic expression of a large part of the genome. This network is regulated at post-transcriptional and post-translational level. Post-translational regulation of clock proteins is essential to ensure stable rhythms and robust timekeeping. Unlike the genes in the TTFL network, modifiers of clock proteins at post-translational level are conserved across taxa. SUMO, a small ubiquitin-related post-translational modifier, regulates timekeeping in mammals through modification of the clock transcription factor BMAL. In this study, SUMO is shown to contribute to oscillator function in Arabidopsis plants. Methods have been developed to prove that mutant lines defective in SUMO machinery, including SUMO-ligase and -protease mutants, display long circadian rhythms. Additionally, sumoylation on the crucial plant clock transcription factor CCA1 is observed in vivo. A fraction of the protein is sumoylated across the expression window of CCA1, with the phase of peak sumoylation in advance of peak total CCA1. The effect of sumoylation of CCA1 was investigated with respect to localisation, stability and DNA binding affinity of the protein, as these are previously described possible effects of sumoylation. The subcellular location of CCA1-YFP fusions in protoplasts was not altered in mutant lines of the SUMO machinery. In vitro experiments show that sumoylation negatively affects the affinity of CCA1 to its cognate promotor element, suggesting that SUMO could act as a reversible attenuator of CCA1 activity. Furthermore, effects of SUMO machinery mutations appear to be differential across a range of physiologically relevant temperatures, implying that sumoylation could be involved in the response to or buffering against fluctuating ambient temperatures. There is an increasing amount of evidence to suggest that metabolic oscillations are not only driven by transcriptional outputs of the clock, but are to some extent self-sustained and can feed timing information back into the clock. Glutathione was investigated as a possible metabolic feedback signal. Expression of clock gene CCA1 was found to be abolished in a mutant of the rate-limiting enzyme for glutathione synthesis (pad2-1). Surprisingly however, the amount of glutathione was not found to oscillate. Combined, the results discussed in this thesis provide a substantial advance on our understanding of post-translational regulation and the integration of metabolic and environmental information into the plant circadian clock.
Keywords: circadian; sumoylation; Arabidopsis; PTM; glutathione; temperature